Methodological implications of intra- and inter-facet microwear texture variation for human childhood paleo-dietary reconstruction: Insights from the deciduous molars of extant and medieval children from France. (June 2020) - Bas, Marlon; Le Luyer, Mona; Kanz, Fabian; Rebay-Salisbury, Katharina; Queffelec, Alain; Souron, Antoine; Willman, John; Bayle, Priscilla
Highlights: Intra-facet microwear variation in children can affect intra-population studies. Non-dietary ontogenetic factors may influence microwear formation in children. Intra-facet microwear variation must be accounted for when comparing individuals. Abstract: The present study concerns occlusal dental microwear texture variation on the deciduous molars of children. A description and evaluation of microwear texture variation within facet 9 and a comparison of microwear textures between grinding facets 9 and 11 are presented. The relationship between wear facet surface area and intra-facet microwear texture variability is evaluated. The sample is composed of naturally-exfoliated, taphonomy-free deciduous second molars from twelve extant children and four archaeologically-derived medieval children (for a total of 51 surface measurements). Dental microwear texture analysis (DMTA) was performed using a confocal microscope and scale-sensitive fractal analysis (SSFA) at three standardized locations on facet 9, and one location on facet 11. Facet shape was visually assessed and scored using a headset magnifier (3×) and composite images (20× confocal microscopy). Individuals were assigned to two groups based on a qualitative assessment of facet surface area. Microwear texture variability within facet 9 was high relative to the variability of microwear textures between individuals. No significant inter-facet variation between facets 9 and 11 was detected. No clear differences in microwear and variabilities within facet 9 were found between individuals assigned to small and large facet groups. Our study shows the existence of important intra-facet microwear variation in a sample of children. Intra-facet microwear variation can affect the ability of DMTA to distinguish between diets in contexts with small sample sizes and subtle differences in diet – such as those characterizing dietary transitions in children. Results also suggest non-dietary factors may influence microwear formation during dental exfoliation. A better understanding of intra-facet microwear variation, and when and how to account for it, can improve the application of occlusal DMTA in similar contexts.